2017
DOI: 10.1007/s00453-017-0366-5
|View full text |Cite
|
Sign up to set email alerts
|

On Unrooted and Root-Uncertain Variants of Several Well-Known Phylogenetic Network Problems

Abstract: The hybridization number problem requires us to embed a set of binary rooted phylogenetic trees into a binary rooted phylogenetic network such that the number of nodes with indegree two is minimized. However, from a biological point of view accurately inferring the root location in a phylogenetic tree is notoriously difficult and poor root placement can artificially inflate the hybridization number. To this end we study a number of relaxed variants of this problem. We start by showing that the fundamental prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Unrooted minimum hybridization. In [29], it was shown that computing the TBR distance for a pair of unrooted binary phylogenetic trees T and T is equivalent to a problem that is concerned with computing the minimum number of extra edges required to simultaneously explain T and T . To describe this problem precisely, let N be an unrooted binary phylogenetic network on X, and let T be an unrooted binary phylogenetic tree on X.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unrooted minimum hybridization. In [29], it was shown that computing the TBR distance for a pair of unrooted binary phylogenetic trees T and T is equivalent to a problem that is concerned with computing the minimum number of extra edges required to simultaneously explain T and T . To describe this problem precisely, let N be an unrooted binary phylogenetic network on X, and let T be an unrooted binary phylogenetic tree on X.…”
Section: Preliminariesmentioning
confidence: 99%
“…where the minimum is taken over all unrooted binary phylogenetic networks on X that display T and T . The value h u (T, T ) is known as the hybridization number of T and T [29].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasize that unrooted phylogenetic networks (as defined here and in e.g. [23,44,21,40]) should be viewed as undirected analogues of rooted phylogenetic networks, which correspond to directed graphs [29]. This is to distinguish them from split networks which are phylogenetic data-visualisation tools and which have a very different phylogenetic interpretation; these are sometimes also referred to as "unrooted" networks [36].Display graphs involving networks are relevant because of the growing number of optimization problems, traditionally posed on rooted trees and networks, which are now being mapped to the unrooted setting (see e.g.…”
mentioning
confidence: 99%
“…This is to distinguish them from split networks which are phylogenetic data-visualisation tools and which have a very different phylogenetic interpretation; these are sometimes also referred to as "unrooted" networks [36].Display graphs involving networks are relevant because of the growing number of optimization problems, traditionally posed on rooted trees and networks, which are now being mapped to the unrooted setting (see e.g. [31,44,27,21]). We prove that, if N displays T -i.e.…”
mentioning
confidence: 99%